2020
DOI: 10.3389/fpls.2020.572540
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome and Proteome Analysis of Salt-Tolerant and Salt-Sensitive Sweet Potato and Overexpression of IbNAC7 Confers Salt Tolerance in Arabidopsis

Abstract: Salt stress is one of the major devastating factors affecting the growth and yield of almost all crops, including the crucial staple food crop sweet potato. To understand their molecular responses to salt stress, comparative transcriptome and proteome analysis of salt-tolerant cultivar Xushu 22 and salt-sensitive cultivar Xushu 32 were investigated. The results showed the two genotypes had distinct differences at the transcription level and translation level even without salt stress, while inconsistent express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 83 publications
2
28
0
Order By: Relevance
“…Meanwhile, the correlation analysis of the transcriptome and proteome showed that the correlation between gene and protein expression was very weak in the late stage. Similar to multiple other studies [ 36 , 37 ], the results showed that not all mRNA: protein ratios reflected the corresponding changes in transcription and protein levels [ 38 ], which was due to the possible occurrence of posttranscriptional regulation during the C. gloeosporioides response in the walnut fruit bracts.…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, the correlation analysis of the transcriptome and proteome showed that the correlation between gene and protein expression was very weak in the late stage. Similar to multiple other studies [ 36 , 37 ], the results showed that not all mRNA: protein ratios reflected the corresponding changes in transcription and protein levels [ 38 ], which was due to the possible occurrence of posttranscriptional regulation during the C. gloeosporioides response in the walnut fruit bracts.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the tremendous increase in the number of multi-omics-based studies in the last couple of years is no surprise. However, following the conventional pattern of information collection, these studies are set for model plants and salt-sensitive crops ( Peng et al, 2018 ; Arefian et al, 2019 ; Meng et al, 2020 ). Analysis of the gene expression of halophytes with a coordinated omics approach, on the other hand, has more potential to dissect the master regulators of salt stress physiology and biochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…To date, NAC TFs have been identified in numerous plant species, such as A. thaliana ( Ooka et al, 2003 ; Li et al, 2021 ), rice ( Oryza sativa ) ( Nuruzzaman et al, 2010 ), tobacco ( Nicotiana tabacum ) ( Li et al, 2018 ), tomato ( Jin et al, 2020 ), broomcorn millet ( Panicum miliaceum ) ( Shan et al, 2020 ), and white pear ( Pyrus bretschneideri ) ( Gong et al, 2019 ). Recently, the roles of IbNAC7 in salt tolerance ( Meng et al, 2020 ) and IbNAC1 against wounding stress ( Chen et al, 2016a ; Chen et al, 2016b ) have been documented while 12 novel IbNAC genes in response to salt stress have been cloned ( Meng et al, 2018 ). Despite these findings, detailed information about the NAC gene family at the genome-wide level has not been available, until now.…”
Section: Introductionmentioning
confidence: 99%